Pengaruh Financial Literacy dan Uang Saku terhadap Perilaku Pengelolaan Keuangan dengan Financial Self Efficacy sebagai Variabel Moderating - Lestiani, Diyah; Bahtiar, Moh. Danang (Politeknik Negeri Jember, 2024)
The purpose of this research to determine whether financial self-efficacy can moderate the influence of financial literacy and pocket money on the financial management behavior of class XI accounting and finance students at SMKN 1 Surabaya 2023/2024 academic year. Using descriptive research with quantitative approach. The primary data collection technique uses questionnaire on the pocket money, financial self-efficacy and financial management behavior variables, while the financial literacy variable uses multiple choice test questions according to PISA standards adapted characteristics of Indonesian students. Data processing and analysis techniques use SEM-PLS analysis. The research results show that financial literacy influences financial management behavior, pocket money influences financial management behavior, financial self-efficacy can moderate the influence of financial literacy on financial management behavior, and financial self-efficacy cannot moderate the influence of pocket money on financial management behavior of class XI AKL SMKN 1 Surabaya. In this research, financial self-efficacy acts as quasi moderator.